ORIENTASI KEWIRAUSAHAAN DAN KINERJA KEUANGAN PENGEMBANGAN PRODUK BARU USAHA MIKRO DAN KECIL - Perminas Pangeran (Jurnal Riset Manajemen dan Bisnis, 2011)
ABSTRACT The purpose of this study is to examine the effect of entrepreneurial orientation on performance in new product development. Drawing upon a sample of 129 micro and small sized firms, multiple regression was used for testing three hypotheses. The results reveal that risk taking and proactiveness influence performance in new product development, while innovativeness show no such effect. Keywords: Innovativeness, Risk taking, Proactiveness, New Product